3x + 4y = -5
-3x -3x
4y= -3x -5
/4 /4
y= -3/4x-5/4
3x + 3y = -2
-3x -3x
3y = -3x-2
/3 /3
y= -1x-2/3
28/x = 40/100
Cross multiply
40x = 28(100)
40x = 2800
Divide both sides by 40
x = 70 students
Answer:
60 miles
Step-by-step explanation:
let d = distance to the lake
Using: time = distance ÷ speed
Create expressions for the time it takes for each journey:
Drive: ![t_1=\dfrac{d}{30}](https://tex.z-dn.net/?f=t_1%3D%5Cdfrac%7Bd%7D%7B30%7D)
Walk: ![t_2=\dfrac{d}{4}](https://tex.z-dn.net/?f=t_2%3D%5Cdfrac%7Bd%7D%7B4%7D)
If total time = 17 hours
![\implies t_1+t_2=17](https://tex.z-dn.net/?f=%5Cimplies%20t_1%2Bt_2%3D17)
![\implies \dfrac{d}{30}+\dfrac{d}{4}=17](https://tex.z-dn.net/?f=%5Cimplies%20%5Cdfrac%7Bd%7D%7B30%7D%2B%5Cdfrac%7Bd%7D%7B4%7D%3D17)
![\implies \dfrac{17d}{60}=17](https://tex.z-dn.net/?f=%5Cimplies%20%5Cdfrac%7B17d%7D%7B60%7D%3D17)
![\implies 17d=1020](https://tex.z-dn.net/?f=%5Cimplies%2017d%3D1020)
![\implies d=\dfrac{1020}{17}](https://tex.z-dn.net/?f=%5Cimplies%20d%3D%5Cdfrac%7B1020%7D%7B17%7D)
![\implies d=60](https://tex.z-dn.net/?f=%5Cimplies%20d%3D60)
Therefore she walked 60 miles
<h2>
Question:</h2>
Find k if (x+1) is a factor of 2x³ + kx² + 1
<h2>
Answer:</h2>
k = 1
<h2>
Step-by-step explanation:</h2>
The factor of a polynomial F(x) is another polynomial that divides evenly into F(x). For example, x + 3 is a factor of the polynomial x² - 9.
<em>This is because;</em>
i. x² - 9 can be written as (x - 3)(x + 3) which shows that both (x - 3) and (x + 3) are factors.
ii. If x = -3 is substituted into the polynomial x² - 9, the result gives zero. i.e
=> (-3)² - 9
=> (9) - 9 = 0
Therefore, if (x + a) is a factor of a polynomial, substituting x = -a into the polynomial should result to zero. This also means that, if x - a is a factor of a polynomial, substituting x = a into the polynomial should give zero.
<em><u>From the question</u></em>
Given polynomial: 2x³ + kx² + 1
Given factor: x + 1.
Since x + 1 is a factor of the polynomial, substituting x = -1 into the polynomial should give zero and from there we can calculate the value of k. i.e
2(-1)³ + k(-1)² + 1 = 0
2(-1) + k(1) + 1 = 0
-2 + k + 1 = 0
k - 1 = 0
k = 1
Therefore the value of k is 1.
Answer:
wrong as his calculation was incorrect at initial level itself when he found the result of the division
Step-by-step explanation:
Andre said
3 ÷ ![\frac{2}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B3%7D)
![=3 \times \frac{3}{2}](https://tex.z-dn.net/?f=%3D3%20%5Ctimes%20%5Cfrac%7B3%7D%7B2%7D)
![=\frac{3 \times 3}{2}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B3%20%5Ctimes%203%7D%7B2%7D)
![=\frac{9}{2}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B9%7D%7B2%7D)
but andre calculated it as
![=4\tfrac{1}{3}](https://tex.z-dn.net/?f=%3D4%5Ctfrac%7B1%7D%7B3%7D)
![=\frac{4 \times 3 + 1}{3}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B4%20%5Ctimes%203%20%2B%201%7D%7B3%7D)
![=\frac{13}{3}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B13%7D%7B3%7D)
Hence his calculation was incorrect at initial level itself